Adecuación de suelos para el cultivo de arroz - riego en Colombia - Prieto V., Oscar; Riobueno, Carlos; Pinto M.A., Roberto; Gamero V., Galo; Zalazar B., Yezid (Instituto Colombiano Agropecuario - ICA, 1992)
Arroz-Oryza sativa